P-223 Implementing social work led carers groups with a co-designed evaluation tool. (19th November 2022) - Powell, Emma; Evans, Tricia; Warren, Jenny; Wanowski, Caron; Ford, Liz
Abstract : Introduction/Background: Caring for a loved one with a complex and incurable condition is a challenging and exhausting experience (Hudson, Remedios & Thomas, 2010. BMC Palliat Care. 9:17). Assessments of carers by Palliative Care Social Workers at Compton discovered resulting fatigue, anxiety and isolation. Research shows that peer support groups offer support which cannot be found in professional-client interactions (Munn-Giddings & McVicar, 2007. Health Soc Care Community.15:26). Aim: To run a professionally facilitated therapeutic group for members to support one another via shared experiences, and to reduce negative feelings. Methods: A monthly afternoon group was implemented in January 2022 for carers of patients attending the Living Well Service. Facilitated by qualified Social Workers, this offered space for carers to come together for peer support, share experiences and seek advice and support from professionals. Group members co-designed a tool for attendees to self-assess their feelings at the start and end of the group via a number scale and evaluation of feelings. Results: Over three separate groups with four attendees at each, 8 evaluation forms were completed. Seven people reported an improvement in feelings to the maximum score of 5, (positive) with one person reporting feeling the same, (calm). Attendees indicated their need for more frequent groups and as a result an extra group was implemented to receive referrals for carer support from other Compton teams. During the pandemic numbers were limited to four attendees plus two staff, numbers are now increasing as the restrictions lift. Discussion: Carers want to come together with peers to share experiences and gain support and this needs to happen at least twice a month. However, when asked if they wanted to set up their own group, attendees declined, preferring a professional -led approach. The feedback from the evaluation shows that the sessions have a positive impact on mood and wellbeing. More research is needed with a wider scope for quantitative and qualitative feedback, and an emphasis on co-designing further groups/support services for carers.